4(1+2a)=-6a(a-3)

Simple and best practice solution for 4(1+2a)=-6a(a-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(1+2a)=-6a(a-3) equation:


Simplifying
4(1 + 2a) = -6a(a + -3)
(1 * 4 + 2a * 4) = -6a(a + -3)
(4 + 8a) = -6a(a + -3)

Reorder the terms:
4 + 8a = -6a(-3 + a)
4 + 8a = (-3 * -6a + a * -6a)
4 + 8a = (18a + -6a2)

Solving
4 + 8a = 18a + -6a2

Solving for variable 'a'.

Combine like terms: 8a + -18a = -10a
4 + -10a + 6a2 = 18a + -6a2 + -18a + 6a2

Reorder the terms:
4 + -10a + 6a2 = 18a + -18a + -6a2 + 6a2

Combine like terms: 18a + -18a = 0
4 + -10a + 6a2 = 0 + -6a2 + 6a2
4 + -10a + 6a2 = -6a2 + 6a2

Combine like terms: -6a2 + 6a2 = 0
4 + -10a + 6a2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(2 + -5a + 3a2) = 0

Factor a trinomial.
2((2 + -3a)(1 + -1a)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(2 + -3a)' equal to zero and attempt to solve: Simplifying 2 + -3a = 0 Solving 2 + -3a = 0 Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3a = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3a = 0 + -2 -3a = 0 + -2 Combine like terms: 0 + -2 = -2 -3a = -2 Divide each side by '-3'. a = 0.6666666667 Simplifying a = 0.6666666667

Subproblem 2

Set the factor '(1 + -1a)' equal to zero and attempt to solve: Simplifying 1 + -1a = 0 Solving 1 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1a = 0 + -1 -1a = 0 + -1 Combine like terms: 0 + -1 = -1 -1a = -1 Divide each side by '-1'. a = 1 Simplifying a = 1

Solution

a = {0.6666666667, 1}

See similar equations:

| 5y-3=7y | | 7+4n=23 | | 4x-3=2x+38 | | 220+220(0.105)-220(0.1)=x | | 5+5x-6=9 | | 8xn=51 | | 2x*5=4x+13 | | 4(-3k+8)=-6k+2(5k+8) | | Ix-4I=-3 | | 3n+6=16 | | F(x)=cos(pi+x) | | 3y+2=7y+10 | | g(z)=Cos(pi+g) | | 4y+2x=13.50 | | .77=In(y) | | 46=-5(m+3)-7(m-7) | | 0.77=ln(y) | | 0.5x-4=7-x | | 7+2[a-3]=-9 | | -8a+15=-105 | | 4x+2y=13.50 | | H-(-7)=12 | | 4x+2x=13.50 | | -6(a+8)+6(1-8)=-78 | | 7x-5=5x+8 | | -7x-4-4x=9x+4x | | (x^2+10+25)-5=25 | | 2[a-4]+15=13 | | 1x^2=0 | | 5x+2x-5=30 | | 10+3x-4=18 | | 4[2a+2]-17=15 |

Equations solver categories